Effectuation and causation: Propositions about decision making process in business network environments - Lemos, Anderson Queiroz; Andreassi, Tales (Revista de Negócios, 2015)
This theoretical essay focuses on the dichotomous question concerning whether entrepreneurs adopt Effectuation or Causationdecision making models. Decision making is an important theme in the studies of entrepreneurship. However, bothdecision making models that have not beenexplored in the context of business network environments. Due this gap, this theoretical essay proposes to examine how the centrality of the firm in a business network environment contributes to the predominance of entrepreneur’s Effectuation and Causation decision making, with the organizational structure as a moderating mechanism in this process. It is argued here that to the extent that the firm acquires relevant resources while enhances its centrality in the network, changes will take place in the organizational structure of the firm over time forcing the entrepreneur adopt Causation instead of Effectuation. Four propositions support this argument. Business networks are appropriated environments to find evidencesof where and when entrepreneurs are more likely to adopt the Effectuation and Causation decision making models. This essay has practical implications for entrepreneurs who manage their firms in a business network environment: i) not all relations are important for the growth and development of the firm; ii) it is suitable uses Effectuation decision making model when the organizational structure is simple and resources are non-relevant; iii) is recommended entrepreneurs use Causation model when in situations where failures in the decision making could be critical to the growth of the firm. The theoretical framework focuses on the concept of inter-organizational networks, on the transformation of the organizational structure and on the principles of Effectuation and Causation.